Building Point to Point Video Call Application for Local Network as Socket Programming Implementation - Sadina, Talitha Widya; Atmadja, Martono Dwi; Zakaria, Muhammad Nanak; Hudiono, Hudiono (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Video call is a technology to communicate by displaying video and sound. Video calls require a network to communicate, most video call applications use cellular networks for their communication media. However, cellular networks require a server. In order for the application to be used without using a cellular network, the application creation requires a socket. Socket is an API (Application Programming Interface) used by applications to connect with each other. While socket programming is a way to use the API. Other than that, security is also needed in the video call application. Encryption is used on data, especially on the data while communicating with video calls where a communication on a video call can only be listened by the party who is communicating. Therefore, a video call application is made as a form of socket programming implementation so that the video call application does not require a cellular network for the communication process. The range of this video call application is unlimited as long as it is connected to the access point. In additional to its reach, this application is secured in the form of encryption so that when communicating later its security is guaranteed.